In situ substrate-formed biofilms using IDODS mimic supragingival tooth-formed biofilms. Issue 1 (1st January 2018) - Tomás, Inmaculada; Prada-López, Isabel; Quintas, Victor; Carreira, Maria José; Simón-Soro, Áurea; Mira, Alejandro; Balsa-Castro, Carlos
ABSTRACT: This study aimed to compare the bacterial viability and diversity of a substrate-formed biofilm (SF-biofilm) in situ to a supragingival tooth-formed biofilm (TF-biofilm) in the same group of individuals. The impact of the device/disc position and toothbrushing during the formation of SF-biofilm was also assessed. Two tests were run. In test 1, 15 volunteers wore two hemi-splints carrying six discs of human enamel, glass, and hydroxyapatite for 2 days, and were instructed to not perform any oral hygiene measure. Biofilm samples were collected from the substrates and the contralateral tooth and were analysed using CLSM. In five volunteers, half of the biofilm present on the discs and their contralateral teeth were scraped and analysed using 16S pyrosequencing. In test 2, the microscopic analysis was repeated only on the SF-biofilm samples, and the volunteers were allowed to brush their teeth. Multivariate analyses revealed that the donors had a significant effect on the composition of the biofilm, confirming its subject-dependent character. The bacterial composition of the SF-biofilm was similar to the TF-biofilm, with significant differential abundance detected in very few taxa of low abundance. The toothbrushing during the formation of SF-biofilm was the only factor that conditioned the thickness or bacterial viability.